Willingness of private general practitioners to refer suspected tuberculosis patients in Badung District - Ni Putu Eka Purnama Dewi; Anak Agung Sagung Sawitri; Ni Wayan Arya Utami (Universitas Udayana, 2017)
Background and purpose: The national tuberculosis (TB) prevalence study showed that between 2013 and 2014 there was significant proportion of pulmonary TB patients received treatment from private healthcare facilities. Data from Bali Province and Badung District Health Offices revealed that of all suspected TB patients only a few were referred by their private general practitioner. A reward system was created in 2012 by providing credit points to every referral made by the private general practitioner. This study aims to examine association between the reward system, national health insurance scheme and willingness to refer suspected TB patients. Methods: A cross-sectional study was conducted from February to April 2017. A total of 111 private general practitioners who practice at Badung District were interviewed. In addition, medical record from these private general practitioners were also examined. Results: Our study found that as many as 55 (45.95%) of private general practitioners had ever referred suspected TB patients over the last year. The total suspected TB patient being reffered in the last year was 132 cases. A cross checking with the laboratory data revealed that only 47 cases (35.61%) presented at referral laboratory facilities. Multivariate analysis showed that the willingness of private general practitioners to refer suspected TB patient was associated to reward system (AOR=4.62; 95%CI: 1.23-17.32) and supervision from TB officials (AOR=13.07; 95%CI: 3.78-45.13). The enrollment of private general practitioners as a primary healthcare facility under the national insurance scheme was not associated with the willingness to refer suspected TB patients. Conclusions: About half of the private general practitioners have ever referred a suspected TB patient. Supervision from TB officials and a reward system in terms of credit points were associated with the willingness to refer suspected TB patients. Ongoing supervision, providing credit points, and improving referral systems are required to improve case findings and referral of suspected TB patients by private general practitioners